Students’ Perceptions of Pedagogical Change during the COVID-19 Crisis - Adhikari, YamNath (Journal of NELTA Gandaki, 2021)
Pedagogical change during the spread of Novel Corona Virus (COVID-19) crisis in Nepalese academia is being the matter of discussion and many academic institutions claim that they are adopting new pedagogy in their curricular activities during COVID-19 crisis. This study aims to find out the secondary students’ experiences of pedagogical change in language teaching and learning procedure. This paper explores an analysis of how pedagogical change enabled secondary students’ experience of online pedagogy during the COVID-19 crisis to plan and manage their learning procedure. As a qualitative research, it employs internet-based semi-structured interview to investigate participants’ experience of pedagogical change and the ground reality of online pedagogy in Nepalese Academic institution during pandemic situation of COVID-19. This paper also shows that how the pandemic situation affects the learning procedure of the students especially in rural Nepal. Online pedagogy is observed as an alternative mode of education in urban areas where there is minimum ICT infrastructure and a means to widen digital divide in rural areas. The students struggle with limited access to digital technology to manage their online learning and the low level of organizational support cannot help them to continue their learning in the pandemic situation. To support the students in their online learning, formulation and operation of policy in wide-ranging systems need to be developed in practice level to provide skills and facilities of ICT for effective distribution of online pedagogy throughout the nation.